2009
DOI: 10.1063/1.3205102
|View full text |Cite
|
Sign up to set email alerts
|

Diameter dependence of modulus in zinc oxide nanowires and the effect of loading mode: In situ experiments and universal core-shell approach

Abstract: Effect of surface stress on the stiffness of micro/nanocantilevers: Nanowire elastic modulus measured by nano-scale tensile and vibrational techniques

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 23 publications
2
39
1
Order By: Relevance
“…1(c)]. We hereinafter focused on e FS instead of on the conventionally discussed r FS , seeing that the measurement error in the strain is smaller than that in the stress; 15 moreover, the ideal strain (e th , i.e., the e FS in defect-free ZnO NWs) is more insensitive to D than is the ideal strength (r th ), which means that the size effect of r FS is partly contributed by the surface-dominated diameter dependence of YM, 13 whereas that of e FS is mostly defect-dominated. 15 The remarkable scattering of e FS can thus be attributed to the size distribution of critical defects, and their size effect results from the reduction of critical defects with decreasing D, which is in accordance with previous qualitative reports.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1(c)]. We hereinafter focused on e FS instead of on the conventionally discussed r FS , seeing that the measurement error in the strain is smaller than that in the stress; 15 moreover, the ideal strain (e th , i.e., the e FS in defect-free ZnO NWs) is more insensitive to D than is the ideal strength (r th ), which means that the size effect of r FS is partly contributed by the surface-dominated diameter dependence of YM, 13 whereas that of e FS is mostly defect-dominated. 15 The remarkable scattering of e FS can thus be attributed to the size distribution of critical defects, and their size effect results from the reduction of critical defects with decreasing D, which is in accordance with previous qualitative reports.…”
Section: Resultsmentioning
confidence: 99%
“…The experimental details can be found elsewhere; 13 in short, each individual NW was axially aligned with the tensile direction and was loaded by deflecting a cantilever [see Fig. 1(a)].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent MD simulations showed that a core and a shell with different Young's moduli exist in ZnO NWs; the Young's moduli of the core and of the shell are lower and higher than the bulk value, respectively [12]. The elastic modulus varies continuously from the core to the surface as a result of energy minimization [12,24]. Both models used in our work are first-order approximations (assuming step-like modulus distribution in the core and the shell) that at the least explain our experimental results reasonably well.…”
Section: Discussion Of Size Effectsmentioning
confidence: 99%
“…The objectives are twofold: (1) to explain the large discrepancy in experimental results in the literature, and (2) to elucidate the underlying mechanism(s) of the size effects, i.e., the relative importance of the surface and the core of NWs, especially when integrated with computational studies. So far only one study compared the Young's moduli of ZnO NWs under tension and resonance and found considerable difference in the size effects, albeit with very different setups/conditions in the two experimental methods [24].…”
Section: Introductionmentioning
confidence: 99%